Serological and bacteriological diagnosis of Brucella abortus biotype 1 infection in Sprague-Dawley rats - Rahman, M S (The Indian Journal of Animal Sciences, 2005)
Female Sprague-Dawley (SD) rats were inoculated subcutaneously @ 1.01×10? cfu suspension in physiological saline to investigate the serological and bacteriological diagnosis of bovine pathogenic strain of Brucella abortus biotype 1 isolated in South Korea in rat. The SD rats were monitored at regular intervals by serological and bacteriological methods. There was no reciprocal antibody titer in sera of 24 weeks post-infection both through PAT and TAT despite the presence of bacteremia but the reciprocal antibody titers were 1:25 through RBT and 1:100 through MET in infected rats. Whereas, the infected rats revealed positive for brucellosis until 74 weeks post-infection through ELISA. The PAT, TAT, RBT and MET using S1119-3 whole cell antigen and ELISA using S1119-3 whole cell and cytoplasmic protein antigens were evaluated for the first time using sera from rat with brucellosis. It is concluded that ELISA using S1119-3 cytoplasmic protein antigen was a potential candidate as an improved diagnostic method for early diagnosis of brucellosis in rats.